Retrieval of middle and upper atmospheric wind based on non-full circular fringe recorded by Fabry-Perot Inteferometer - Wang, HouMao; Wang, Chong; Wang, YongMei; Zhang, XiaoXin; Huang, Cong; Liang, ShaoLin (Science China. Earth sciences, 2017)
Fabry-Perot Interferometer（FPI） has been used widely for wind measurements of the middle and upper atmosphere.To date, most of FPIs have been based on full-closed circular fringe, which needs 15–25 min to obtain a group of wind velocity（zonal and meridional）. However, it is hard to improve the temporal resolution because full-closed circular fringe in several directions cannot be easily imaged onto the same Charge-Coupled Device（CCD） with enough airglow intensity. In this paper, a data processing method is proposed for non-full circular fringe of FPI, which can support CCD with enough area of observations in several directions simultaneously. The method is focused on the center determination of non-full fringe. It includes radial cross-section, peak coordinate determination, and center calculation. Based on the calculated center, the fringe is annular summed. Then its radius is determined subsequently using Gaussian fitting. Finally, the wind is retrieved from the fringe radius. For validation, fringes from two ground-based FPIs were used, which are deployed in Kelan（38.71°N, 111.58°E） and Xinglong（40.40°N, 117.59°E） in China. The results retrieved from non-full fringes of FPIs were compared with that from full-closed circular fringe. The averaged wind deviation between them demonstrates reasonable difference with 5.38 ms~-（1） for 892.0 nm airglow emission, 5.81 ms~-（1） for 630.0 nm emission, and 3.03 ms~-（1） for 557.7 nm emission. Besides, wind results of Xinglong FPI are compared roughly with measurements of meteor radar which is deployed in Ming Tombs of Beijing（40.3°N,116.2°E）. Good agreement demonstrates that this method is robust enough for FPI wind retrieval of mesosphere and thermosphere.